Basic treatment in natural clinoptilolite for improvement of physicochemical properties - Castro de Souza, Vanessa (2018)
Natural zeolites are low in cost and exhibit interesting properties for applications in adsorption and catalysis. However, the fact that they are natural materials, not obtained in pure form, and can incorporate various compensating ions can compromise their properties and restrict their use. As their textural and chemical properties are of great relevance for adsorption and catalysis applications, this work aims to study the modification of the natural zeolite clinoptilolite to obtain materials with better physicochemical properties. Clinoptilolite was treated with NaOH under various conditions. The treated material was characterized by X-ray diffraction, X-ray fluorescence, N2 adsorption and desorption at 77 K, CO2 adsorption at 273 K, and pyridine adsorption. The treatment allowed the removal of silicon from the material, improving the textural properties and preserving the structural Al. With the removal of Si, the Si/Al ratio decreased, and consequently, the number of acid and adsorptive sites increased. In addition, statistical planning revealed that the concentration of NaOH is the parameter that most influences the improvement of the textural properties.